Hydrophosphorylation of electron-deficient alkenes and alkynes mediated by convergent paired electrolysis. Issue 59 (4th July 2022) - Sun, Xue; Yang, Jianjing; Yan, Kelu; Zhuang, Xinyu; Yu, Jie; Song, Xiaodan; Zhang, Fanjun; Li, Bingwen; Wen, Jiangwei
Abstract : A straightforward and practical strategy for hydrophosphorylation of electron-deficient alkenes and alkynes to access γ-ketophosphine oxides, enabled by CPE strategy in the absence of a metal, base, and redox reagent, has been described. Abstract : A straightforward and practical strategy for hydrophosphorylation of electron-deficient alkenes and alkynes to access γ-ketophosphine oxides, enabled by a convergent paired electrolysis (CPE) in the absence of a metal, base, and redox reagent, has been described. Mechanistic studies have revealed that the diarylphosphane oxides play the dual role of a phosphorus radical precursor and hydrogen donor in this transformation.